Analyzing Poverty in Central Java Through K-Medoids Clustering Method - Khoirunnisa', Asma'; Wibowo, Firdaus Amruzain Satiranandi; Sukowati, Diah (Program Studi Informatika, Universitas Ahmad Dahlan, 2025)
Poverty remains a major issue in Indonesia, particularly in Central Java which has the second highest poverty rate on the island of Java, following the Special Region of Yogyakarta. This study aims to categorize districts and cities in Central Java based on poverty characteristics to support more effective poverty alleviation programs. Using the K-Medoids clustering method, poverty indicators in Central Java Province were analyzed for the year 2021. The K-Medoids method aims to identify poverty groupings and visualize the distribution of poverty in Central Java province for the year 2021. The results identified two clusters. Cluster 1 includes 31 districts and cities with higher poverty rates, lower education levels, and lower residential rental costs. Although the poverty rate is high, people in this cluster show a strong work ethic with relatively low unemployment among those aged over 15 years. In contrast, Cluster 2 shows lower poverty rates, higher education levels, and higher housing costs, but relatively higher unemployment rates. Overall, Cluster 1 represents areas requiring special attention from the government to improve community welfare.